Cytokines in healthy temporomandibular joint synovial fluid. (27th February 2014) - Kristensen, K. D.; Alstergren, P.; Stoustrup, P.; Küseler, A.; Herlin, T.; Pedersen, T. K.
Summary Analysis of temporomandibular joint (TMJ) synovial fluid may elucidate the aetiology of temporomandibular disorders and arthritic conditions, as well as the inflammatory mechanisms involved. Knowledge about healthy synovial fluid is necessary to understand TMJ pathologies. We aimed to quantify the proinflammatory cytokines interleukin (IL)‐1β, IL‐2, IL‐6 and tumour necrosis factor (TNF), and the anti‐inflammatory cytokines IL‐10 and interferon (IFN)‐γ in healthy TMJ synovial fluid to serve as reference values for future studies on TMJ pathologies. Twenty healthy, young adult volunteers without temporomandibular dysfunction were included. Bilateral synovial fluid samples were obtained using the push‐pull technique with hydroxocobalamin described by Alstergren in 1999. Cytokines were quantified with Luminex multiplex assays and compared using nonparametric statistical analysis. No serious adverse effects were reported. Of 40 possible samples, 14 fulfilled the strict sampling criteria and were included in the analysis. Cytokine values (reported as medians with interquartile ranges) were as follows: TNF, 23 (13–37) pg mL−1; IL‐2, 1·8 (0–22) pg mL−1; and INF‐γ, 10 (0–47) pg mL−1. IL‐1β, IL‐6 and IL‐10 were almost undetectable. In addition, TNF and INF‐γ cytokine levels correlated. We demonstrated that TNF was consistently detected and IFN‐γ and IL‐2 sporadically detected in the TMJ synovial fluid of healthy individuals using the hydroxocobalamin method and a multiplex assay. The cytokines IL‐10, IL‐1β and IL‐6 were barely detectable in this sample of healthy TMJs.